A biological product of Bacillus amyloliquefaciens QST713 strain for promoting banana plant growth and modifying rhizosphere soil microbial diversity and community composition - Tian, Libo; Zhang, Wenlong; Zhou, Guang-Dong; Li, Shu; Wang, Yongfen; Yang, Baoming; Bai, Tingting; Fan, Huacai; He, Ping; Zheng, Si-Jun (Frontiers in Microbiology, 2023)
Bananas are not only an important food crop for developing countries, but also a major trading fruit for tropical and semitropics regions, maintaining a huge trade volume. Fusarium wilt of banana (FWB) caused by the Fusarium oxysporum f. sp. cubense is becoming a serious challenge to the banana industry globally. Biological control has potential to offer both effective and sustainable measures for this soil-borne disease. In order to explore the biocontrol effects of the biological agent Bacillus amyloliquefaciens QST713 strain on banana plants, two cultivars Brazilian and Yunjiao No.1 with varied resistance to FWB were used in greenhouse pot experiments. Results showed that the plant height and pseudostem diameter of banana susceptible cultivar Brazilian were increased by 11.68% and 11.94%, respectively, after QST713 application, while the plant height and pseudostem diameter of resistant cultivar Yunjiao No.1 were increased by 14.87% and 12.51%, respectively. The fresh weight of two cultivars increased by 20.66% and 36.68%, respectively, indicating that this biological agent has potential effects on plant growth. Analysis of the rhizosphere soil microbial communities of two different cultivars of banana plants showed that TR4 infection and B. amyloliquefaciens QST713 strain application did significantly affect the bacterial and fungal diversity of Yunjiao No.1, but not in the cultivar Brazilian. Also, TR4 infection and QST713 application could change the bacterial community composition of both banana cultivars, and the fungal community composition of Yunjiao No.1 was also changed significantly. Relevance analysis indicated that the relative richness of Bacillus and Pseudomonas in the rhizosphere of both cultivars increased significantly after QST713 application, which had good positive correlation with plant height, pseudostem girth, aboveground fresh weight, leaf length and leaf width. Therefore, the outcome of this study suggests that this biological agent QST713 strain has potential application in banana production for promoting plant growth and modification of soil microbial communities, particularly in the TR4 infected field.